Developing of Drying Condition on ConvectiveDryer for Talise Wood Grown Naturally at Sulawesi Island - , Y.SURANTO ([Yogyakarta] : Fak. Kehutanan UGM, 2003)
Decreasingsupply of mostof commercialwoodas raw materialinspireforestproductindustryto lookfor uncommercial woodto be utilized.Properutilizationof thesewoodsmustbe basedon the woodproperties,both basic propertiesand processing properties. Drying property is one of the most important one, because proper drying process will be the main key to utilize efficiently and ensure high quality of wood product. Talise(Terminaliacatappa)whichis oneof the uncommercialwoodgrownnaturallyin SulawesiIsland,used by woodworking industry to produce building components'to be exported.l The objective of this research was to develop the drying .schedule of Talise wood. The drying schedule was decided by the result of the quick drying test which is elaborated based on the Terazawa method. Result of the research showed that initial moisture content was 64.10&deg